2021
DOI: 10.3390/admsci12010006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Difficult Coworkers on Employees’ Responses in Macao’s Public Organizations—The Mediating Role of Perceived Stress

Abstract: Difficult coworkers can be found in almost every workplace, including public and private organizations. This paper investigates the effects of difficult coworkers on employees’ responses including intention to leave and mental health through attitude towards difficult coworkers and perceived stress in public organizations. Data were collected from 307 public sector employees in Macao SAR, China. Results of partial least squares–structural equation modeling indicated that difficult coworkers significantly influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 62 publications
(91 reference statements)
0
0
0
Order By: Relevance
“…One sexual harassment item “The person harasses people sexually” had a mean score of 3.07 (SD = 1.964) that was significantly lower than the mid-point at 4.0 ( p < 0.01). The findings were similar to what To and Yu (2022) reported in Macao's public organizations and confirmed that difficult coworkers existed in many workplaces. Results of PLS-SEM indicated that difficult coworkers were characterized by bossiness, followed by unprofessional behavior and busybody.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…One sexual harassment item “The person harasses people sexually” had a mean score of 3.07 (SD = 1.964) that was significantly lower than the mid-point at 4.0 ( p < 0.01). The findings were similar to what To and Yu (2022) reported in Macao's public organizations and confirmed that difficult coworkers existed in many workplaces. Results of PLS-SEM indicated that difficult coworkers were characterized by bossiness, followed by unprofessional behavior and busybody.…”
Section: Discussionsupporting
confidence: 89%
“…Yu and reported that attitude toward difficult coworkers in the form of encountering attitude directly influenced turnover intention. To and Yu (2022) found that attitude toward difficult coworkers influenced turnover intention directly and indirectly through perceived stress. Thus, we hypothesize:…”
Section: Attitude Toward Difficult Coworkers and Turnover Intentionmentioning
confidence: 98%
See 2 more Smart Citations
“…Experts studying the subject agree that good employee relationships contribute to long-term employee engagement, so employers should strive to build a supportive and cohesive workplace community (Alexander et al 1998;Zayed et al 2022). In order to retain employees, the issue of team integration should also be an important consideration during selection, as conflicts arising from the different personalities of employees can lead to the deterioration of employee relations (Allen 2006;Shouman et al 2022;To and Yu 2022;Szentgróti and Tapolczai 2011). If the relationship between direct colleagues is inadequate or there is a conflict, there may be a rivalry in the workplace, which not only negatively affects the quality of work, but may even result in the loss of talented employees (Glew 2012).…”
Section: Coworkersmentioning
confidence: 99%